2016
DOI: 10.1038/ncomms13896
|View full text |Cite
|
Sign up to set email alerts
|

A TLR9 agonist promotes IL-22-dependent pancreatic islet allograft survival in type 1 diabetic mice

Abstract: Pancreatic islet transplantation is a promising potential cure for type 1 diabetes (T1D). Islet allografts can survive long term in the liver parenchyma. Here we show that liver NK1.1+ cells induce allograft tolerance in a T1D mouse model. The tolerogenic effects of NK1.1+ cells are mediated through IL-22 production, which enhances allograft survival and increases insulin secretion. Increased expression of NKG2A by liver NK1.1+ cells in islet allograft-transplanted mice is involved in the production of IL-22 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…While these studies did not assess IL-22 levels or SILT activation, our data suggest one consequence of CpG administration is the activation of SILT-resident macrophages. In fact, islet allograft survival is enhanced by CpG administration resulting in enhanced IL-23 and IL-22 production (48). Therefore, Yet40 + macrophages residing in SILT may be able to acquire and detect microbial products for the production of tissue-protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…While these studies did not assess IL-22 levels or SILT activation, our data suggest one consequence of CpG administration is the activation of SILT-resident macrophages. In fact, islet allograft survival is enhanced by CpG administration resulting in enhanced IL-23 and IL-22 production (48). Therefore, Yet40 + macrophages residing in SILT may be able to acquire and detect microbial products for the production of tissue-protective factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, using an islet allograft transplantation model, we determined that JNK1-defective Tregs prolong islet allograft survival in liver parenchyma more efficiently than wild-type (WT) Tregs. The immunosuppressive environment in the kidney capsule, testis, and liver can protect allogeneic islets from inflammation-mediated destruction in comparison to other organs 19 21 . It has been demonstrated that islet allografts can survive long term in the liver parenchyma 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…The immunosuppressive environment in the kidney capsule, testis, and liver can protect allogeneic islets from inflammation-mediated destruction in comparison to other organs 19 21 . It has been demonstrated that islet allografts can survive long term in the liver parenchyma 21 , 22 . We transplanted an islet allograft into the hepatic parenchyma of chemically induced diabetic (CDM) or non-obese diabetic (NOD) recipient mice with or without JNK1-defective or WT Tregs and determined the islet allograft survival.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MRP8/14-facilitated myeloidderived suppressor cell generation (Petersen et al, 2013) did apparently not contribute to LZT induction as we did not detect an altered LZT reaction in MRP14 KO mice. As demonstrated for other inflammatory disease models, repeated activation by TLR ligands can result in an inhibited receptor-mediated signaling (e.g., TLR7, TLR9, TLR4) toward a subsequent exposition to the corresponding ligand (Biswas and Lopez-Collazo, 2009;Hayashi et al, 2009Hayashi et al, , 2012Julian et al, 2015;Kawai and Akira, 2010) or in active tolerance induction, for example, by activation of regulatory T cells, immunosuppressive dendritic cells, or natural killer cells (as shown for TLR4, TLR7, TLR9) (Caramalho et al, 2003;Forward et al, 2010;Kang et al, 2007;Tripathi et al, 2016). However, the absence of TLR4, TLR7, or TLR9 did not influence the LZT development, excluding that the effect of frequently applied low doses of the contact allergen during LZT induction is regulated by TLR4-, TLR7-, or TLR9-mediated tolerance induction.…”
mentioning
confidence: 79%
“…In particular, nickel triggered proinflammatory signaling via a direct interaction with TLR4 during allergic contact dermatitis development in men and reconstitution of TLR4 signaling in mice restored nickelinduced CHS development (Schmidt et al, 2010). In contrast, several studies revealed that stimulation of TLRs such as TLR4, TLR7, or TLR9 can also result in activation of tolerancepromoting immune cells (Caramalho et al, 2003;Forward et al, 2010;Tripathi et al, 2016) or in a hyporesponsive state of TLRs after repeated exposures to the same ligand as shown for TLR4 (lipopolysaccharide/endotoxin tolerance), TLR7, and TLR9 (Biswas and Lopez-Collazo, 2009;Hayashi et al, 2009;Julian et al, 2015). Furthermore, the myeloidrelated proteins (MRPs) 8 and 14 (or known as alarmins S100A8 and S100A9), serving as ligands for TLR4, were required for the development of myeloid-derived suppressor cells, leading to a significantly enhanced CHS reaction in the absence of these molecules in MRP8/MRP14 knockout (KO) mice (Petersen et al, 2013).…”
mentioning
confidence: 99%